The diversity of post-fire regeneration strategies in the cerrado ground layer - Pilon, Natashi A. L.; Cava, Mário G. B. [UNESP]; Hoffmann, William A.; Abreu, Rodolfo C. R.; Fidelis, Alessandra [UNESP]; Durigan, Giselda (Wiley, 2020)
Disentangling species strategies that confer resilience to natural disturbances is key to conserving and restoring savanna ecosystems. Fire is a recurrent disturbance in savannas, and savanna vegetation is highly adapted to and often dependent on fire. However, although the woody component of tropical savannas is well studied, we still do not understand how ground-layer plant communities respond to fire, limiting conservation and management actions. We investigated the effects of prescribed fire on community structure and composition, and evaluated which traits are involved in plant community regeneration after fire in the cerrado ground layer. We assessed traits related to species persistence and colonization capacity after fire, including resprouter type, underground structure, fire-induced flowering, regeneration strategy and growth form. We searched for functional groups related to response to fire, to shed light on the main strategies of post-fire recovery among species in the ground layer. Fire changed ground-layer community structure and composition in the short term, leading to greater plant species richness, population densities and increasing bare soil, compared with unburned communities. Eight months after fire, species abundance did not differ from pre-disturbance values for 86% of the species, demonstrating the resilience of this layer to fire. Only one ruderal species was disadvantaged by fire and 13% of the species benefited. Rapid recovery of soil cover by native vegetation in burned areas was driven by species with high capacity to resprout and spread vegetatively. Recovery of the savanna ground-layer community, as a whole, resulted from a combination of different species traits. We summarized these traits into five large groups, encompassing key strategies involved in ground-layer regeneration after fire. Synthesis. Fire dramatically changes the ground layer of savanna vegetation in the short term, but the system is highly resilient, quickly recovering the pre-fire state. Recovery involves different strategies, which we categorized into five functional groups of plant species: grasses, seeders, bloomers, undergrounders and resprouters. Knowledge of these diverse strategies should be used as a tool to assess conservation and restoration status of fire-resilient ecosystems in the cerrado.
Keywords: below-ground bud bank; fire ecology; fire response; fire-prone ecosystems; functional traits; herbaceous species; neotropical savanna; underground structures